Formation of the legal basis for the use of electronic information technologies in criminal proceedings and proceedings on cases of administrative offenses - Kuzhabaeva, G.M.; Kaliev, A.K. (Bulletin of the Karaganda University “Law Series”, 2022)
The beginning of the XXI century was marked by the active growth of scientific and technological progress, which led to the penetration of computer and digital technologies into all spheres of human activity. The informatization of society through the introduction of innovative systems has acquired a global character, becoming one of the most important factors in its development. The purpose of this research is to form the legal basis for the use of electronic information technologies in criminal proceedings and proceedings on cases of administrative offenses. Methodological basis of the study comprises the content analysis of normative legal acts with the use of the formal-logical method and the method of system analysis. As a result, the need to overcome the semantic and textual indifference of the current legislation in the context of regulatory regulation of the use of electronic information technologies in pre-trial criminal and administrative proceedings is revealed. It is assumed that this will significantly save the procedural time of the participants in the process, reduce the “cost” of the proceedings and ensure its speed by bringing the moment of committing the offense as close as possible to the time of their resolution in court